2005
DOI: 10.12693/aphyspola.108.705
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Study of Bulk GaN Doped with Beryllium

Abstract: Photoluminescence of bulk GaN:Be grown by high pressure method is presented. The investigated crystals show well-resolved photoluminescence due to free and bound excitons similar to that observed for homoeptitaxial GaN layers. In addition to the excitonic transitions, pronounced luminescence band at 3.38 eV, due to Be acceptor, is observed. It was found that temperature behavior of this emission is typical of donor-and conduction band-acceptor transitions. The optical activation energy of Be acceptor is obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The properties of the UVL Be band are the same as obtained earlier from the study of Be-doped GaN grown by MBE [7,9,11] or the high nitrogen pressure solution (HNPS) method. [10] In particular, the donor-acceptor-pair (DAP) peaks transform into the conduction band-acceptor (eA) peaks with increasing temperature (Figure 2). This transformation is typical for acceptors in GaN.…”
Section: The Uvl Be Bandmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of the UVL Be band are the same as obtained earlier from the study of Be-doped GaN grown by MBE [7,9,11] or the high nitrogen pressure solution (HNPS) method. [10] In particular, the donor-acceptor-pair (DAP) peaks transform into the conduction band-acceptor (eA) peaks with increasing temperature (Figure 2). This transformation is typical for acceptors in GaN.…”
Section: The Uvl Be Bandmentioning
confidence: 99%
“…Photoluminescence (PL) studies have repeatedly shown that the Be Ga acceptor has a level shallower than Mg, yet the resultant GaN:Be material is commonly semi-insulating. [5][6][7][8][9][10] Previous reports on PL from Be-doped GaN are almost exclusively based on GaN grown by molecular beam epitaxy (MBE). Our systematic studies of MBE-grown GaN:Be samples revealed three Be-related PL bands: the ultraviolet luminescence (UVL Be ) band with a maximum at 3.38 eV, the yellow luminescence (YL Be ) band with a maximum at 2.2 eV, and the red luminescence (RL Be ) band with a maximum at 1.8 eV.…”
mentioning
confidence: 99%